If people were money: Estimating the potential gains from increased international migration - Jonathon W. Moses; Bjørn Letnes (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
In this paper we elaborate on the findings produced by an applied equilibrium model that is used to calculate the annual efficiency gains from free international migration. These findings suggest that we can expect significant gains from liberalizing international labour flows. In particular, we expand on two implicit aspects of the estimates: the actual number of migrants being generated by the various counter-factual scenarios, and the per-migrant cost/benefits associated with each. These estimates are then compared with contemporary migration flows and the findings of studies that analyse their economic impact. In light of these comparisons, we conclude that our original findings are not unreasonable.
Keywords: C68; F22; J61; N30; O15; 330; international migration; efficiency gains; immigration surplus; development; CGE models; Internationale Wanderung; Allgemeines Gleichgewicht; Migrationstheorie